2013
DOI: 10.1590/1516-4446-2011-0746
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome prevalence in different affective temperament profiles in bipolar-I disorder

Abstract: Objective: Temperament originates in the brain structure, and individual differences are attributable to neural and physiological function differences. It has been suggested that temperament is associated with metabolic syndrome (MetS) markers, which may be partly mediated by lifestyle and socioeconomic status. Therefore, we aim to compare MetS prevalence between different affective temperamental profiles for each season in bipolar patients. Methods: Twenty-six bipolar type-I patients of a specialized outpatie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…Unlike bipolar I disorder, which is defined by discrete and full‐blown manic episodes, the conceptualization of SBP (and ‘bipolar II spectrum’) is based on an unstable temperamental substrate in the context of which protracted or brief hypomanic episodes occur with alterations in depression . Indeed, a growing body of evidence suggests that affective temperaments that have genetic underpinnings play a big role in the relationship of morningness‐eveningness to mood fluctuation and in the treatment response , and are associated with comorbid conditions such as alcohol dependence and the metabolic syndrome . Furthermore, such temperamental attributes as mood labile , energy activity , and day dreaming – characteristics of the CT described by Kretschmer – are commonly seen in bipolar II disorder and may be the predictors of switching to bipolar II from depression .…”
Section: Discussionmentioning
confidence: 99%
“…Unlike bipolar I disorder, which is defined by discrete and full‐blown manic episodes, the conceptualization of SBP (and ‘bipolar II spectrum’) is based on an unstable temperamental substrate in the context of which protracted or brief hypomanic episodes occur with alterations in depression . Indeed, a growing body of evidence suggests that affective temperaments that have genetic underpinnings play a big role in the relationship of morningness‐eveningness to mood fluctuation and in the treatment response , and are associated with comorbid conditions such as alcohol dependence and the metabolic syndrome . Furthermore, such temperamental attributes as mood labile , energy activity , and day dreaming – characteristics of the CT described by Kretschmer – are commonly seen in bipolar II disorder and may be the predictors of switching to bipolar II from depression .…”
Section: Discussionmentioning
confidence: 99%
“…This has already been argumented and documented for several of these comorbidities and in particular, anxious, ADHD, impulsecontrol, and eating disorders [42]. Even chronic medical conditions were shown to be preferentially associated with temperamental traits, particularly the depressive ones [65,66]. These data suggest that some temperamental profiles and/or association of temperamental traits may condition the more or less early occurrence of comorbidities which could themselves constitute risk factors for the further development of affective disorders.…”
Section: Discussionmentioning
confidence: 64%
“…Accordingly, our findings also fall in the same direction -cyclothymic, depressive and anxious temperament scores were associated with the SPAQ scores. In this regard, we previously reported that temperamental dimensions constitute a vulnerability factor for the seasonal influence in a study investigating metabolic syndrome prevalence across affective temperament profiles (Altinbas et al 2013). On the other hand, the SPAQ scores were associated with neither irritable nor hyperthymic temperament scores in the current study.…”
Section: Discussionmentioning
confidence: 97%